Antimicrobial Activity of Various Plant Extracts on Pseudomonas Species Associated with Spoilage of Chilled Fish - Bahurmiz, Osan Maroof; Ahmad, Rosma; Ismail, Noryati; Adzitey, Frederick; Sulaiman, Shaida Fariza (Turkish Science and Tecnology (TST), 2016)
The antimicrobial activity of various plant extracts on Pseudomonas bacteria isolated from spoiled chilled tilapia (Oreochromis sp.) was evaluated in this study. In the first stage of this study, red tilapia was subjected to chilled storage (4°C) for 3 weeks, and spoilage bacteria were isolated and identified from the spoiled fish. Pseudomonas was the dominant bacteria isolated from the spoiled fish and further identification revealed that P. putida, P. fluorescens and Pseudomonas spp. were the main species of this group. In the second stage, methanolic extracts of 15 selected plant species were screened for their antimicrobial activity, by agar disc diffusion method, against the Pseudomonas isolates. Results indicated that most of the extracts had different degrees of activity against the bacterial isolates. The strongest activity was exhibited by bottlebrush flower (Callistemon viminalis) extract. This was followed by extracts from guava bark (Psidium guajava) and henna leaf (Lawsonia inermis). Moderate antimicrobial activities were observed in extracts of clove (Syzygium aromaticum), leaf and peel of tamarind (Tamarindus indica), cinnamon bark (Cinnamomum zeylanicum), wild betel leaf (Piper sarmentosum) and fresh thyme (Thymus spp.). Weak or no antimicrobial activity was observed from the remaining extracts. The potential antimicrobial activity shown by some plant extracts in this study could significantly contribute to the fish preservation.